2000
DOI: 10.1002/1521-396x(200011)182:1<465::aid-pssa465>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Deeper Comprehension of the Interaction Mechanisms between Mesoporous Silicon and NO2

Abstract: The high sensitivity of a room‐temperature porous silicon NO2 sensor has required an investigation of surface dynamics between NO2 and mesoporous silicon. By means of electrical measurements in gas atmosphere and in‐situ FTIR, evidence of a new interaction mechanism strongly affecting the electrical conductivity of the porous silicon (PS) sensors has been found. Absorption bands have been attributed to NO2—, suggesting carrier transfer from the silicon wires to NO2, thanks to its high electronic affinity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Although the detailed geometrical features, which might play key roles in deciding sensor performances, were highly dependent upon the preparing conditions, the integral sponge structure was the most important and commonest characteristics of all PS samples [1,2]. Just as found in detecting humidity [6,7], nitrogen dioxide [8][9][10][11], ethanol gas [12][13][14], and various organic vapors [3,15,16], PS-based sensors showed an improved sensitivity but a relatively long response time, which were attributed to the greatly enlarged sensing area formed in PS and the absence of effective gas transportation pathways in the sponge structure, respectively. In previously published papers, we have reported that an effective pathway for gas transportation could be built in a silicon nanoporous pillar array (Si-NPA) * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detailed geometrical features, which might play key roles in deciding sensor performances, were highly dependent upon the preparing conditions, the integral sponge structure was the most important and commonest characteristics of all PS samples [1,2]. Just as found in detecting humidity [6,7], nitrogen dioxide [8][9][10][11], ethanol gas [12][13][14], and various organic vapors [3,15,16], PS-based sensors showed an improved sensitivity but a relatively long response time, which were attributed to the greatly enlarged sensing area formed in PS and the absence of effective gas transportation pathways in the sponge structure, respectively. In previously published papers, we have reported that an effective pathway for gas transportation could be built in a silicon nanoporous pillar array (Si-NPA) * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Rurali et al carried out quantum chemical simulations of NO 2 molecules adsorption on SiNWs and gave their own explanation of the experimental results obtained in Refs. . One can mark out the following main experimental facts presented in Refs.…”
Section: Review Of Results Of the Experimental And Theoretical Investmentioning
confidence: 78%
“…According to our data, two groups of authors and most extensively studied the effect of nitric oxide on mesoporous silicon (m‐PS) structures. Boarino et al investigated the conductivity, Fourier‐spectra of infrared absorption (FTIR), EPR spectra, Raman, and MAS‐NMR spectra of m‐PS samples, placed in NO 2 atmosphere. By measuring the free holes concentration at different NO 2 pressures, authors determined absorption energy of NO 2 on the m‐PS surface based on the Langmuir isotherms.…”
Section: Review Of Results Of the Experimental And Theoretical Investmentioning
confidence: 99%
See 2 more Smart Citations